Effect of sound absorption and screen height on spatial decay of speech – Experimental study in an open-plan office. (September 2020) - Keränen, Jukka; Hakala, Jarkko; Hongisto, Valtteri
Abstract: Room acoustic parameters of open-plan offices, e.g. ceiling, wall, screen, and furniture absorption, and screen height between workstations, affect strongly sound pressure level (SPL) of speech. The effect depends on the distance from the speaker. The aim of this experimental study was to examine the effect of ceiling, wall, and screen absorption, and screen height on the spatial decay of speech both at short and long distances from the speaker. Twenty-two experimental conditions were built in an open-plan office including 12 workstations. The conditions were combinations of ceiling absorption (2 levels), wall absorption (2 levels), screen absorption (2 levels), and screen height (4 levels). The spatial decay of A-weighted SPL of speech was measured according to ISO 3382-3 in workstations at distances from 2 to 9 m from the speaker. The A-weighted SPL of speech in the nearest workstation, at the distance of 2 m, varied between 53 and 61 dB, and at the distance of 4 m, between 46 and 60 dB. The spatial decay rate of A-weighted SPL of speech, D 2, S, varied between 1.3 and 8.5 dB. The results confirmed that ceiling absorption is the most efficient way to increase spatial attenuation, but the attenuation effect also depends on the absorption of vertical surfaces like screens and walls, and the height of the screens. Our study is unique because it is the first experimental study conducted in a full-scale open-plan office, which investigates the impact of several sound absorbing surfaces and screen height simultaneously.